Penguatan Kapasitas UMKM Dodol Al Arabi Samarinda melalui Digitalisasi Bisnis dan Optimalisasi Manajemen Keuangan - Maulana, Indra; Rahmatullah, Dedy; Norsita, Mega; Daffaa, Atiiqah; Monashafa, Siti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the Indonesian economy; however, they continue to face fundamental challenges, particularly in financial management and digital marketing strategies. These issues are also encountered by the partner of this community engagement program, Dodol Al Arabi in Samarinda City, which has been operating conventionally without systematic financial recording, a written business plan, or digital-based promotional strategies. This program aims to strengthen the business capacity of the partner through the improvement of financial management and the optimization of digital marketing. The methods applied include socialization, training, workshops, individual mentoring, and evaluation. The interventions cover the implementation of a basic bookkeeping system, the development of a written business plan based on the Business Model Canvas (BMC), and assistance in utilizing digital media for product promotion. The results indicate that the partner is now able to conduct financial recording in a more systematic manner, calculate the Cost of Goods Sold (COGS), and design a more structured business plan. In addition, the partner has begun to utilize social media platforms for product promotion, although further mentoring is required to ensure consistency and professionalism. Overall, this program provides tangible contributions to strengthening the managerial and marketing capacity of the partner while potentially generating broader socio-economic impacts, such as the creation of new job opportunities, the reinforcement of local supply chains, and the preservation of Samarinda’s traditional culinary heritage. This program also offers novelty by integrating financial management strategies and digital marketing into real implementation at the micro-business level based on local products.